The anomalous magnetic moment of the muon in the Standard Model : an update - Aliberti, R.; Zhevlakov, A.S.; Bijnens, J. ; 0000-0002-1618-2844; Hermansson-Truedsson, Nils ; 0000-0003-3619-2916 (Physics Reports, 2025)
We present the current Standard Model (SM) prediction for the muon anomalous magnetic moment, aμ, updating the first White Paper (WP20) [1]. The pure QED and electroweak contributions have been further consolidated, while hadronic contributions continue to be responsible for the bulk of the uncertainty of the SM prediction. Significant progress has been achieved in the hadronic light-by-light scattering contribution using both the data-driven dispersive approach as well as lattice-QCD calculations, leading to a reduction of the uncertainty by almost a factor of two. The most important development since WP20 is the change in the estimate of the leading-order hadronic-vacuum-polarization (LO HVP) contribution. A new measurement of the e+e−→π+π− cross section by CMD-3 has increased the tensions among data-driven dispersive evaluations of the LO HVP contribution to a level that makes it impossible to combine the results in a meaningful way. At the same time, the attainable precision of lattice-QCD calculations has increased substantially and allows for a consolidated lattice-QCD average of the LO HVP contribution with a precision of about 0.9%. Adopting the latter in this update has resulted in a major upward shift of the total SM prediction, which now reads aμSM=116592033(62)×10−11 (530ppb). When compared against the current experimental average based on the E821 experiment and runs 1–6 of E989 at Fermilab, one finds aμexp−aμSM=38(63)×10−11, which implies that there is no tension between the SM and experiment at the current level of precision. The final precision of E989 (127 ppb) is the target of future efforts by the Theory Initiative. The resolution of the tensions among data-driven dispersive evaluations of the LO HVP contribution will be a key element in this endeavor.
Publisher Copyright: © 2025 The Author(s)
Keywords: Anomalous magnetic moment of the muon